2019
DOI: 10.5070/p2cjpp11243090
|View full text |Cite
|
Sign up to set email alerts
|

Transitory Legality: The Health Implication of Ending DACA

Abstract: This paper examines the effects of the rescission announcement of the DACA program on the health outcomes of Latino DACA recipients in California. Research shows that undocumented immigrants face poorer health outcomes than their documented counterparts and U.S. citizens, and that being offered legal status (e.g. DACA) considerably improves their health outcomes. Even though studies have examined the impact of shifting legal status on incorporation, to our knowledge no studies have considered the effects of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Unsurprisingly, we show that the beneficial effects of DACA on sleep behavior tend to dissipate from 2016. This finding is consistent with the idea that the uncertainty around this temporary program may have undermined its positive impact on health and well-being, and, in turn, on sleep (Mallet and Garcia Bedolla, 2019).…”
Section: Introductionsupporting
confidence: 90%
“…Unsurprisingly, we show that the beneficial effects of DACA on sleep behavior tend to dissipate from 2016. This finding is consistent with the idea that the uncertainty around this temporary program may have undermined its positive impact on health and well-being, and, in turn, on sleep (Mallet and Garcia Bedolla, 2019).…”
Section: Introductionsupporting
confidence: 90%
“…Specifically, the DACA program was rescinded by former President Donald Trump in 2017 and the U.S. Supreme Court was weighing the legality of this action and determining the future of the program in the months we fielded the survey. Prior research has established that the rescission and subsequent political threats limited the protective effects of DACA and created new strains (Benuto et al, 2018;Mallet & Garcia Bedolla, 2019;Morales Hernandez & Enriquez, this issue). This suggests that liminal legal statuses like DACA are insufficient to promote recipient's integration and a path to citizenship will be critical to promote undocumented student's academic success and overall well-being.…”
Section: Legal Vulnerabilitymentioning
confidence: 99%
“…For instance, two policies of the Trump administration that are especially likely to be linked to negative health outcomes are the 2017 repeal of DACA and the ongoing separation of families at the border between the US and Mexico (Bouza et al, ; Hainmueller et al, ; MacKenzie et al, ). Previous research has assessed the health impacts of the DACA, and its repeal, (Hainmueller et al, ; Mallet & Bedolla, ; Patler et al, ) and family separation (Bouza et al, ; MacKenzie et al, ) and has demonstrated the negative health effects of both policies in the Latino, immigrant, and Latino immigrant populations, and especially for children.…”
Section: Resultsmentioning
confidence: 99%